Gender issues: Trajectories of change in the Italian mediascape. Issue 2 (2nd January 2023) - Buonanno, Milly; Faccioli, Franca
Beyond single works scattered across different publication venues, Italian scholarship on gender and media has hardly circulated abroad. This Special Issue is, therefore, meant to make a substantial contribution to the international visibility and consideration of a body of works that has so far remained in the shadows. From this perspective, the varied range of the articles in the issue offers an overview of both the current status of gender and media studies in Italy and the ways gender is constructed in discourses, practices and actions throughout the Italian media landscape – including television, radio, fashion magazines, newspapers and digital platforms. In addition to the variety of media and topics, the works collected in this issue are also peculiar for resorting frequently to the historiographic approach, on the assumption that trajectories of change in gender and media relationship can only be traced in the comparison between past and present.